2023
DOI: 10.1126/sciadv.adg6072
|View full text |Cite
|
Sign up to set email alerts
|

Perception versus reality: Implications of elephant hunting by Neanderthals

Abstract: Neanderthals hunted elephants at Neumark-Nord 1 (Germany), a finding that has major implications for our understanding of social and cultural aspects of Neanderthal behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…• The authors additionally suggested a recipe of a "Neanderthal flat bread" requiring up to 10 processing steps (Graham, 2022) Recent data from a German site demonstrate that Neanderthals, 125 ka ago, were able to hunt and kill up to 13 tons heavy straight-tusked elephants (Paleoloxadon antiquus). Processing them further required an estimated 200−600 person hours and would then provide more than 2500 daily portions of 4000 calories per person, suggesting that they also had preservation technologies to store the food (Gaudzinski-Windheuser et al, 2023;Starkovich, 2023). This indicates that our early predecessors were already quite skilled in preparation and processing of foods.…”
Section: Origin and Historymentioning
confidence: 99%
“…• The authors additionally suggested a recipe of a "Neanderthal flat bread" requiring up to 10 processing steps (Graham, 2022) Recent data from a German site demonstrate that Neanderthals, 125 ka ago, were able to hunt and kill up to 13 tons heavy straight-tusked elephants (Paleoloxadon antiquus). Processing them further required an estimated 200−600 person hours and would then provide more than 2500 daily portions of 4000 calories per person, suggesting that they also had preservation technologies to store the food (Gaudzinski-Windheuser et al, 2023;Starkovich, 2023). This indicates that our early predecessors were already quite skilled in preparation and processing of foods.…”
Section: Origin and Historymentioning
confidence: 99%